Interrelationships among growth hormone, thyroid function, and endocrine-disrupting chemicals on the susceptibility to attention-deficit/hyperactivity disorder - Wang, Liang-Jen; Huang, Ying-Hua; Chou, Wen-Jiun; Lee, Sheng-Yu; Chang, Hsin-Yu; Chen, Chih-Cheng; Chao, How-Ran (European child & adolescent psychiatry, 2023)
Abnormal growth hormones and thyroid function may be linked to pathophysiology of attention-deficit/hyperactivity disorder (ADHD). Phthalates and bisphenol-A (BPA), two endocrine-disrupting chemicals (EDCs), may affect the human endocrine system. In this study, we aimed to perform a comprehensive investigation of whether growth hormone, thyroid function, and EDCs exhibited differential levels between ADHD patients and healthy controls. In total, 144 children with ADHD and 70 healthy control subjects were enrolled. Their endocrine systems were evaluated using the serum levels of insulin-like growth factor-1 (IGF-1), IGF-binding protein-3 (IGFBP-3), thyroid-stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4), and Free T4. The urinary levels of EDCs, including monoethyl phthalate (MEP), mono-methyl phthalate (MMP), monoethylhexyl phthalate (MEHP), mono-n-butyl phthalate (MnBP), monobenzyl phthalate (MBzP), and BPA, were also examined. Patients with ADHD had lower IGF-1 levels than healthy controls ( p = 0.003), but we observed no significant difference in IGFBP-3, TSH, T3, T4, or Free T4. Compared to the control group, patients with ADHD demonstrated higher MEHP levels ( p = 0.043), MnBP ( p = 0.033), and MBzP ( p = 0.040). Furthermore, MEHP levels ( p < 0.001) and BPA levels ( p = 0.041) were negatively correlated with IGF-1 levels, while IGF-1 levels were negatively correlated with principal components consisting of ADHD clinical symptoms and neuropsychological performance variables. We suggest that MEHP exposure may be associated with decreased serum levels of IGF-1 and increased risk of ADHD. The mechanism underlying this association may be important for protecting children from environmental chemicals that adversely affect neurodevelopment.